Use of tricyclic antidepressants in trigeminal neuralgia - Margute, Tiago Garcia; Ferreira , Palloma Cristina; Almeida , Isabela Maria Moura; Denardin, Caio; Silva , Thiago Quirino Mota da; Margute , Túlio Garcia; Maione, Max Soares; Rossato, Andrei Rabenschlag; Santos, Igor Fonseca dos (Jour Med Resh and Health Sci, 2022)
Trigeminal neuralgia is one of the neuropathic pains most commonly found in the head and neck region. It presents in painful episodes in the form of electric shock lasting from seconds to two minutes, when trigger points are triggered in intra and extraoral regions. Classified as a chronic pain, trigeminal neuralgia is capable of catastrophically altering the patient’s quality of life. With the review of articles in Portuguese language, articles in English language, books and journals searched in databases such as LILACS, PUBMED and SCIELO, a survey of existing data from the year 1993 to the year 2018 was carried out, and the words used to per-form this research were tricyclic antidepressants, trigeminal neuralgia, neuropathic pain and dentistry. This study aims to understand how trigeminal neuralgia occurs and to evaluate the possible treatments for it, focusing on the pharmacological treatment with tricyclic antidepressants, aiming to provide a positive result in the treatment of pain. And so we found positive results of the action of these drugs on the pathology.